Power transient analysis of fuel-loaded reflector experimental devices in Jules Horowitz Material Testing Reactor. (August 2016) - Console Camprini, P.; Sumini, M.; Artioli, C.; Gonnier, C.; Pouchin, B.; Sireta, P.; Bourdon, S.
Abstract: The Jules Horowitz Reactor (JHR) is designed to be the 100 MW Material Testing Reactor (MTR) which achieves the most important experimental capacity in Europe. It has been conceived to perform several irradiation tests at a time – taking advantage of many positions both in the core and in the reflector. The locations inside the reflector zone may utilize an intense thermal neutron flux to test the properties of fuel materials and to produce radioisotopes for medical purposes. High sample irradiation rates are achieved in the reflector area and a relevant power can be generated here, due to fissile materials inside these fuel test samples: about 60 kW for ADELINE test devices, some 120 kW for MADISON and up to about 650 kW for MOLFI. Then, power transient analyses are requested for these devices, mainly in connection with the reactor shutdowns. Energy deposition in the fuel samples – which are placed in the reflector – has been evaluated considering both normal operation and different reactor shutdown procedures. The analysis has been carried out by dividing the reactor system into two portions: the core as a neutron source and the reflector as a subcritical system. First, core power transients have been simulated by means of DULCINEE point kinetics code. Then, the neutron flux inside the reflector has been evaluated through the Monte Carlo transport code TRIPOLI 4.8, starting from the previously computed source. Both nominal operation and different configurations of control rod insertions have been taken into account. This evaluation provided a description of core-device coupling in terms of flux shape in the reflector. Main focus is on power deposition in samples which is of course affected by flux shape. Thus, point kinetics approach has been applied to the core as a source irradiating the samples that are considered coupled through the parameters evaluated by Monte Carlo. Power transients have been calculated both for energy deposition due to neutron-induced fission reactions and for gamma radiation as well. Results matched technical needs for the cooling loops optimization and the safety scenarios.